A divisão subgenérica de Trypoxylon Latreille, 1796 (Hymenoptera: Crabronidae) é sustentada por marcadores moleculares? - Sabadini, Camila Pereira (2018)
The family Crabronidae comprises a group of extreme importance to the phylogeny of Hymenopytera and is considered by some authors to be the group that gave rise to bees. Despite this importance, very few studies have been conducted on the family. Trypoxylon is the most diverse genus in Crabronidae, with 631 species. Females supply of their nests with spiders, which are paralyzed and deposited in brood cells arranged linearly in pre-existing cavities or in nests of mud built by the females. The genus is divided into two subgenera based on morphological and behavioral characteristics. Trypoxylon (Trypoxylon) sensu stricto is the most diverse and has no synapomorphies that sustain it as a monophyletic group. Nevertheless, the subgenus Trypoxylon (Trypargilum) is characterized by the guard behavior displayed by males. Although studies on the subgenus Trypoxylon (Trypargilum) have been developed in Brazil, few investigations have addressed the subgenus Trypoxylon (Trypoxylon) or the phylogeny of the genus, which becomes more difficult due to the lack of specialists in the country that can perform the taxonomical identification of these organisms. The use of molecular markers in genetic evolutionary studies is an option for cases like Trypoxylon and enables the study of the evolutionary history of the genus. Therefore, the following question was raised and served as the basis for the present study: "Is the subgeneric division of Trypoxylon Latreille, 1796 (Hymenoptera: Crabronidae) supported by molecular markers?" To answer this question, we extracted and sequenced the pol, CytB and COI regions of 268 samples of the genus Trypoxylon. We also searched on databases and found 173 sequences of the COI gene. These sequences were subjected to analyses of nucleotide diversity, phylogenetic analysis by Bayesian Inference and Maximum Likelihood and estimated time of divergence as well as the delimitation and identification of species. The results showed that the nuclear gene pol is less varied in comparison to the mitochondrial genes CytB and COI, which were good candidates for the study of intraspecific and interspecific variation. The molecular data had high support values for the division of the subgenera into Trypoxylon (Trypoxylon) and Trypoxylon (Trypargilum). However, the findings suggest that there may be more than two subgenera in the genus Trypoxylon. The species delimitation analyses demonstrated the same results in most cases, but the inconsistencies encountered resemble the difficulties found in the classification, strongly suggesting the need for a revision of the group based on morphological traits and molecular markers.